Genome-wide profiling and predicted significance of post-mortem brain microRNA in Alzheimer's disease - Henriques, Adriane D.; Machado-Silva, Wilcelly; Leite, Renata E. P. [UNESP]; Suemoto, Claudia K. [UNESP]; Leite, Katia R. M. [UNESP]; Srougi, Miguel [UNESP]; Pereira, Alexandre C. [UNESP]; Jacob-Filho, Wilson [UNESP]; Nobrega, Otavio T.; Brazilian Aging Brain Study Grp (Elsevier B.V., 2020)
Background: MicroRNAs (miRNAs) emerged as regulatory elements, with up to 70 % of all miRNAs found in the brain, playing key roles in the onset of Alzheimer's disease (AD). Objective: to broadly assess the expression levels of miRNAs in post-mortem brain (PMB) samples of individuals deceased with or without AD. Methods: A high-throughput micmarray platform was used to sketch miRNA samples isolated from superior and middle temporal gyrus of A+T+ AD cases, compared to samples from age- and sex-matched AD-devoid donors, all pulled from the University of Sao Paulo's Brain Biobank. The miRNAs identified by microarray were subjected to validation with specific qRT-PCR assays employing independent PMB samples. Results: The analyses yielded 6 miRNAs differentially expressed (miR-30e_3p; miR-365b_5p; miR-664_3p; miR1202; miR-4286; miR-4449), and their interplay with specific AD-related genes and signaling pathways was explored using bioinformatics analyses (including the KEGG package, mirPath v.3). In the end, 3 miRNAs, 7 target genes and 11 pathways were found closely interrelated and implicated with the AD pathophysiology. Conclusion: A dysregulation on a subset of these miRNAs appear to affect a range of genes (notably PTEN) and pathways (emphasis to PI3K-AKT) so to provide grounds for neuronal death by apoptotic signaling, autophagy and/or oxidative damage.
Keywords: Alzheimer's disease; microRNA; Array analysis; DIANA miRPath